Navigating the evolving landscape in the prescribing of medications for insomnia in Singapore: Principles and considerations from a psychiatrist’s perspective - Ho Teck Tan; Chao Tian Tang; Shian Ming Tan (Annals, Academy of Medicine, Singapore)
There are significant challenges for medical practitioners who have to navigate complex clinical, legal, ethical and administrative considerations in the prescription of controlled medications in the treatment of insomnia. This commentary examines the changing landscape and reframing of risks associated with the use of benzodiazepines and Z-drugs in light of recent legal precedents based on the frameworks of the Ethical Code and Ethical Guidelines, and the Prescribing of Benzodiazepines Guidelines (MOH Clinical Practice Guidelines 2/2008). The recent ruling from the Court of Three Judges has shone a spotlight on rigorous justification in instances where there is deviation from established treatment guidelines and thorough risk-benefit analysis, particularly when considering off-label use of medications, which is not uncommon in the clinical setting. While the risks of long-term prescription of benzodiazepines should never be discounted, preservation of a patient’s functioning and current quality of life should also be taken into consideration in the risk-benefit analysis. The complexities of transitioning patients from sedative hypnotics to alternative medications are also addressed, with an advocation for licensed medications with established safety profiles.